Gliosarcoma with Chondrosarcomatous Differentiation: A Case Report - B, Rajeshwari; Shanmugam, Salapathi; Niamath, Sadiya; Ghosh, Mitra; Ghosh, Siddhartha (Annals of Pathology and Laboratory Medicine, 2019)
Gliosarcoma (GS) is a variant of IDH wild type of glioblastoma (WHO grade IV). It is characterized by biphasic tissue pattern showing glial and mesenchymal components. The glial component is usually similar to glioblastoma and the sarcomatous component is usually spindle cell type. Rarely the sarcomatous component can show additional lines of mesenchymal differentiation like cartilage, bone, smooth muscle, skeletal muscles etc. These tumours are more firm and discrete because of the high content of reticulin and collagen in the sarcomatous component. Originally these tumours were thought to arise from sarcomatous transformation of proliferating blood vessels or dedifferentiation of an advanced glioma. The recent studies show that both glial and sarcomatous component show identical mutations in p53, PTEN and TERT genes and suggest a monoclonal origin from a common stem cell. There is no significant difference in prognosis between glioblastoma and gliosarcoma. Here we report a case of gliosarcoma with chondrosarcomatous differentiation in a 52 year old gentleman. The case is presented here for its rarity.